Pendampingan Sistem Jaminan Halal dan Pengembangan Produk Kopi Di Kecamatan Ulu Belu, Kabupaten Tanggamus - Eka Nur’azmi Yunira; Deni Subara; Wilda Harlia Devita; Borneo Satria Pratama (CV. Multi Kreasi Media, 2022)
Tanggamus was the second largest coffee producer in Lampung Province. Ulubelu was one of the districs that had the highest coffee productivity in Tanggamus. Coffee price from farmer for green bean product was Rp 20.380 per kilogram while for red picking coffee bean was more expensive. Only a few farmer had SME to process coffee into its derivative products. This activity aims to make farmer aware of the importance of handling coffee and developing cofee derivative products. This activity was also purposed to increase coffee productivity for marketing through halal certification and improving coffee products quality. The method of this community service were preparation, survey, workshop post-harvest handling and production of coffee derivatives, training and assistance of halal certification. The result of this community service were farmer interest to developed derivative products of coffee, and there were 4 SME from 2 group of farmer that had received halal certification from this activity.